ПУҚАРАЛАРДЫҢ ЖЕКЕ ҲУҚЫҚЛАРЫ ҲӘМ ОЛАРДЫҢ КОНСТИТУЦИЯЛЫҚ ТӘРЕПТЕН ҚОРҒАЛЫЎЫ - Исмаилова, З. (SCIENCE and SOCIETY, 2016)
The person and his rights are one of the main problems at present. The highest value of our state is protection of the person, his life and other inalienable laws. The Constitution of the Republic of Uzbekistan, laws and the reports, all this are the basic source in protection of the personal rights of citizens and the person.